Affection and participation in family-school relationship in covid-19 times: The classroom multigrade case in the rural community “San Antonio de Cusicancha” (Revista Peruana de Investigación Educativa, 2023)
This study addresses the logics of participation and affection in the family-school relationship, in lights of the changes produced by the Covid-19 pandemic, which has generated a series of scenarios that have transformed different aspects of social life in the Andean communities. In this sense, my main objective was explored how the logic of affection and participation are related in the family-school relationship in a multigrade classroom of an elementary school in the “San Antonio de Cusicancha” rural community, in the context of the current pandemic. For this, I took the theoretical contributions, which are had in the country, regarding family participation in the school context, and, in lights of the contributions of the ontological turn and the affective turn in anthropology, I addressed the affections, from the questioning reason-emotion, product of the discussion of said contributions. Thus, through telephone calls, I used methodologies like interviews, file analysis, biographical method and some participation exercises to find out the perceptions of the participants. At the end of the study, I conclude the undoubted relationship that exists between the affections and participation in the family-school relationship, since both areas would contribute to the link that educational actors, families, teachers, boys and girls, exercise from their agencies, which they would be supported by their trajectories and the ways of perceiving the world, and, in which the community also plays a relevant role. However, these relationships are conditioned by factors that are linked to the great inequalities in which Andean rural schools live.
Keywords: affection; parent participation; parent school relationship; rural education; pandemics